Treatment adherence behaviors and asthma control: The role of treatment perception - Lugo-González, Isaías (2020)
Background: In the case of asthma, one of the problems faced by patients and health services is the poor adherence to maintenance medication, which limits disease control. Treatment perception (necessity for treatment and concern for adverse effects of treatment) has been one of the psychological variables that has been best associated with this problem. The aim of this study was to evaluate, compare and relate the treatment perception, adherence behaviors and disease control in Mexican adults with asthma. Method: 267 adults with asthma from Mexico City participated, who responded to an evaluation battery. Results: The main results show that patients with high perceived necessity of treatment and low concern about the adverse effects of treatment are more adherent and have better asthma control than patients with high necessity and high concern with low necessity and low concern. In addition, it was identified that a high concern favors poor adherence and this, negatively impacts asthma control. Conclusion: To improve adherence, it is necessary to increase the need to reduce concern.